Immunogenicity and estimation of antibody persistence following vaccination with an inactivated virosomal hepatitis A vaccine in adults: A 20-year follow-up study. Issue 10 (7th March 2017) - Chappuis, Francois; Farinelli, Tiziana; Deckx, Henri; Sarnecki, Michal; Go, Oscar; Salzgeber, Yvonne; Stals, Coby
Highlights: A 20-year prospective follow-up study of Epaxal®, inactivated hepatitis A vaccine. Seroprotection rate was 100% (⩾10 mIU/mL cut-off) at 20-year follow-up visit. Median duration of protection against hepatitis A (⩾10 mIU/mL cut-off) was 77.3 years. Protection prediction for 95% participants was ⩾41.5 years with ⩾10 mIU/mL cut-off. Protection prediction for 95% participants was ⩾33 years with ⩾20 mIU/mL cut-off. Abstract: Purpose: This was a 20-year follow-up study to assess long-term persistence of protective antibody levels against the hepatitis A virus (HAV) in healthy participants vaccinated with 2 doses of inactivated hepatitis A vaccine (Epaxal®) between 1992 and 1995. Methods: Blood samples for anti-HAV antibody concentrations were obtained during a follow-up visit 20 years after vaccination and were analyzed in parallel with samples still available from previous visits using AxSYM® HAVAB 2.0 assay. Results: Mean (SD) age of the participants was 44.71 (3.905) years at year 20 follow-up (N = 95). Participants completing 0/12-month Epaxal® immunization regimen (N = 94) had seroprotection rate of 100% (95% CI: 96.2, 100.0) with ⩾10 mIU/mL seropositivity cut-off and 98.9% (95% CI: 94.2, 100.0) with ⩾20 mIU/mL cut-off. With ⩾10 mIU/mL cut-off, the estimated median duration of protection was 77.3 years (95% CI: 71.8, 83.5) with 95% of the vaccinated participants predicted to be protected for at least 41.5 years. At ⩾20 mIU/mL cut-off, the estimated median duration of protection was 64.8 years (95% CI: 60.1, 68.4) with 95% of the vaccinated participants predicted to be protected for at least 33 years. Anti-HAV antibody geometric mean concentrations were higher in women (277.9; 95% CI: 217.7, 354.7) than in men (167.7; 95% CI: 125.2, 224.6). Conclusion: The data from this 20-year follow-up study confirm previous observations that two doses of Epaxal® provide protection against hepatitis A infection for at least 30 years in over 95% of healthy participants.